(untitled) (The Review of Diabetic Studies, 2025)
Introduction- Type 2 diabetes mellitus frequently leads to diabetic kidney disease, a major cause of chronic kidney disease and cardiovascular morbidity. Early detection remains challenging due to limitations of serum creatinine and albuminuria. Cystatin C has emerged as a potentially more sensitive biomarker. This study comparatively evaluates these markers for early renal dysfunction detection. Material and Method- This cross-sectional study included 90 adults with type 2 diabetes. Patients with advanced kidney disease were excluded. Serum creatinine, cystatin C, HbA1c, estimated glomerular filtration rate (eGFR), and urine albumin-to-creatinine ratio (ACR) were measured. Early renal dysfunction was defined as eGFR 60–89 mL/min/1.73m² and/or microalbuminuria. Statistical analysis was performed using SPSS. Result- Among 90 patients with type 2 diabetes (mean age 52.4±7.8 years), 80% had microalbuminuria despite preserved eGFR. Serum cystatin C was significantly higher in microalbuminuria and showed stronger correlations with ACR and eGFR than creatinine. ROC analysis demonstrated superior diagnostic accuracy for cystatin C (AUC 0.84). Multivariate analysis identified cystatin C, diabetes duration, and HbA1c as independent predictors of microalbuminuria. Conclusion- Serum cystatin C demonstrated superior diagnostic accuracy compared to creatinine for early renal dysfunction in type 2 diabetes. Its strong association with microalbuminuria supports its role as a sensitive biomarker for early detection and improved risk stratification in diabetic kidney disease.